مستوى الطموح و علاقته بالصحة النفسية لدى عينة من تلاميذ البكالوريا دراسة ميدانية في ثانوية عمر دهينة و ثانوية محمد الصادق طالبي في ولاية الأغواط - الفاسي زهرة; معمري منصورة; عمومن رمضان (My University, 2018)
The current study aims to identify the relationship between the level of ambition and mental health and to know the differences in the level of ambition and mental health of the two experimental science and philosophical literature for both sexes in the baccalaureate students. The current study started from the following questions. the following hypotheses were suggested: 1- There is a statistically significant relationship in the level of ambition and mental health among baccalaureate students. 2- There are no statistically significant differences in the level of ambition attributed to the variable sex (male, female) among baccalaureate students. 3- There are no significant differences in the level of ambition attributed to the variable division (experimental science, literature philosophy). 4- There were no statistically significant differences in mental health due to the gender variable (males, females). 5- There are no statistically significant differences in mental health due to the variable of the division (experimental sciences, philosophy literature). The study was conducted according to the descriptive approach, as it is best suited to describe the characteristics of the phenomenon and to gather information about it and follow it in the field to obtain real data. This was done by applying the first two surveys on the level of ambition by Dr. Ziad Barakat and the second on mental health by Dr. Bushra Ahmed Jassim Okasha. The two questionnaires were applied to a sample of 80 baccalaureate students from the Experimental Science Division and the philosophy literature department of Omar Dehayna Secondary School and Mohammed Sadiq Talabi Secondary School. The sample was randomly selected. After collecting and processing the data, we obtained the following results: 1- There is no statistically significant relationship between the level of ambition and mental health of baccalaureate students. 2- There were no statistically significant differences in the level of ambition attributed to the sex variable (male, female) among the baccalaureate students. 3- There are no statistically significant differences in the level of ambition attributed to the variable division (experimental sciences, philosophy literature). 4- There were no statistically significant differences in mental health due to the gender variable (males, females). 5- There are no statistically significant differences in mental health due to the variable of the division (experimental sciences, philosophy literature). The results were discussed in light of the theoretical and previous studies The study concluded with a series of suggestions.